Influence of spacing and intercropping on biomass and essential oil yield of patchouli [Pogostemon cablin (Blanco) Benth.] - Singh, Munnu (Journal of Spices and Aromatic Crops, 2008)
A field experiment was carried out in a semi-arid tropical climate at Bangalore (Karnataka) toinvestigate the influence of spacing (60 cm x 45 cm and 75 cm x 45 cm) and intercroppingsystems (patchouli sole crop, patchouli + blackgram, patchouli + soybean, patchouli + Frenchbean and patchouli + lady's finger) on the biomass and essential oil yield and oil quality ofpatchouli (Pogostemon cablin (cv. Johore). The spacing of 60 cm x 45 cm was superior to 75cm x 45 cm and produced 11.6 t ha-1 total biomass yield (total of two harvests; 12.1% higherthan that of 75 cm x 45 cm spacing) and 88.9 kg ha-1 total essential oil yield (10.9% greaterthan that of 75 cm x 45 cm). Intercropping with legumes and vegetables did not affect totalbiomass yield and total essential oil yield of patchouli and yielded 0.40, 0.35, 5.40 and 4.50 tha-1 over and above that of patchouli sole crop. Quality of oil was not influenced by plantspacing and intercropping systems. Maximum gross return was obtained with patchouli +French bean (Rs.1,66,470/-) followed by patchouli + lady's finger (Rs.1,51,770/-).